Bearing the Neoconservative Burden? Frontline Work in Prisons - McElligott, Greg (Social justice, 2007)
A study was conducted to examine corrections officers (COs) in the privatized prison sector. Data were obtained from a review of the literature and from interviews with COs at a private prison in Canada. Findings revealed that COs are most accurately viewed as front-line workers under pressure from management initiatives that intensify and de-skill their work, and that COs occupy an exposed part of an increasingly coercive regime. Findings suggest that, despite the support of public and private officials for private “supermax” prisons, the business models used by private companies could make automated surveillance and remote control technologies more dangerous in private hands. Findings imply that technology makes a poor substitute for the skilled work of COs.